Prevention of Radicalism and Terrorism in Riau Province to Maintain National Security - Yudi Rusmanto; Syamsunasir Syamsunasir; Anang Puji Utama; Pujo Widodo; Herlina Juni Risma Saragih (CV. AFDIFAL MAJU BERKAH, 2023)
Terrorism arises due to radical attitudes that culminate in individuals inspired to commit destructive acts and even kill those who are considered a threat, as a means to commit jihad for him or her. It cannot be denied that the development of terrorist networks in Indonesia has begun to expand to the corners of the region scattered throughout Indonesia. Riau is a region that is also included as one of the targets and hideouts for Indonesian terrorist network perpetrators. This is because Riau is directly adjacent to two countries which have the potential to become an area and target for terrorist operations, as Riau is the entry point for world trade in the region. In the last six years, namely, from 2016 to 2021, there was an act of terrorism in Riau each year, which started with radicalism and then manifested by acts of terror. The method used in this study is a qualitative approach. Data Collection was done through literature studies and direct interviews, which were then analyzed through National Security theory. With the increase in radicalism and acts of terrorism, the Riau government, Riau Police, and TNI namely Korem 031 Wira Bima should have a strategy and synergy to prevent massive radicalism and terrorism in Riau Province, to maintain National Security